Short-term response of ground-dwelling arthropods to storm-related disturbances is mediated by topography and dispersal - Davide Nardi; Filippo Giannone; Lorenzo Marini (Basic and Applied Ecology, 2022)
Wind disturbances and consequent salvage logging lead to drastic changes in forest soil conditions, vegetation and microclimate, potentially affecting arthropod communities. In mountain regions, topography is expected to be particularly important to modulate the effect of canopy removal and soil disturbance potentially amplifying the ecological contrast between forest and disturbed areas. Here, we studied the short-term response of ground beetles (Carabidae), spiders (Araneae), and harvestmen (Opiliones) in wind-damaged spruce forests along statistically orthogonal gradients in elevation, slope, and aspect. We addressed three main ecological questions: (i) Does the effect of wind disturbance on diversity depend on topography? (ii) Are there specific taxon-related responses to disturbances?, and (iii) What is the role of dispersal in shaping species assembly dynamics? We generally observed that increasing slope and elevation amplified the differences between undisturbed forest and windfall areas. On the one hand, the diversity of ground beetles and harvestmen seemed to be negatively affected by wind disturbance, causing a loss of specialized forest species with a low rate of colonization of species typical of open habitats. On the other hand, several novel spider species were able to rapidly colonize windfalls and community composition strongly shifted from forest to disturbed areas. Species with long-range dispersal strategies (e.g. flying and ballooning) were those more likely to colonize windfalls. Our findings suggest that disturbance effects on ground-dwelling organisms were modulated by underlying environmental gradients and that short-term response of different taxa was dependent on their dispersal ability.